THE PRINCIPAL MANAGEMENT IN ENTREPRENEURSHIP DEVELOPMENT IN NAHDLATUL ULAMA MODEL JUNIOR HIGH SCHOOL - Yogi DM, Muhamad (ASWAJA: Jurnal Pendidikan dan Keislaman, 2025)
This study aims to describe the principal's management of NU Model Middle School in developing entrepreneurship within the school environment. The research background stems from the importance of instilling an entrepreneurial spirit from an early age to develop an independent, creative, and innovative generation in facing global challenges. The study used a qualitative approach with descriptive methods. Data were collected through interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing.The results indicate that the principal's management in developing entrepreneurship encompasses four main functions. First, planning, which involves setting goals, strategizing, providing resources, and developing an entrepreneurship program integrated with the curriculum. Second, organizing, which includes formulating goals, dividing work, assigning personnel according to competencies, delegating authority, and coordinating with internal and external parties. Third, implementation, which emphasizes visionary leadership, fostering entrepreneurial attitudes and morals, effective communication, providing incentives, and discipline. Fourth, monitoring, which is carried out through setting standards, evaluating performance, comparing results with targets, and correcting deviations.The conclusion of this study confirms that the principal's management of NU Model Middle School plays a significant role in building a conducive entrepreneurial climate within the school. Well-planned, organized, well-executed, and continuously supervised management can foster student independence, creativity, innovation, and competitiveness.